[PP.12.17] EVALUATION OF SELECTED PARAMETERS OF NEURO-HORMONAL ACTIVITY AND RETINAL AND INTRARENAL PERFUSION IN PATIENTS WITH POLYCYTHEMIA VERA. (September 2016) - Wojcicki, J.; Sikorska, A.; Kaszuba, A.; Harazny, JM.; Lewandowski, J.; Sinski, M.; Binczyk, E.; Szymanek, K.; Prejbisz, A.; Szaflik, JP.; Gosk-Przybylek, M.; Janas, J.; et al.
Abstract : Objective: Polycythemia vera (PV) is a myeloproliferative neoplasm primarily characterized by erythrocytosis. There is limited data on frequency and pathogenic mechanism of HT in patients with PV. Therefore the aim of the study is to present a selected clinical, neuro-humoral and hemodynamic characteristics of HT in patients with PV. Design and method: In the on-going study we included 20 consecutive patients (13F, 7 M, mean age 62 ± 9 years) with PV diagnosed (according to the WHO criteria) in one clinical center and 10 age, gender, body mass index, blood pressure (BP) and number of medication (p > 0.05) matched patients with essential HT (EHT). All patients underwent detailed clinical investigation which included among others: office and ambulatory BP measurements (ABPM), hormonal evaluations (renin, aldosterone and plasma metanephrines) and Doppler duplex ultrasound examination of renal arteries (resistive index [RI] was evaluated). Retinal microperfusion (RCF) and retinal arterioles were assessed using scanning laser Doppler flowmetry (SLDF). The parameters of retinal morphology were determined by automatic full-field perfusion imaging analysis (AFFPIA V.4.011). Muscle sympathetic nervous activity (MSNA) was evaluated by microneurography. Results: Hypertension on office or ABPM was present in 15 patients with PV (75%). Patients with PV as compared with EHT patients were characterized by less pronounced BP fall at night. There were: a trend towards lower serum aldosterone concentration and significantly lower plasma free epinephrine levels (25.9 ± 8.5 vs 36.8 ± 12.7 pg/mL; p = 0.048) in patients with PV. Patients with PV were characterized by lower 24 h heart rate on ABPM (63 ± 7 vs 75 ± 11 beats/min; p = 0.006) and lower MSNA as compared with EHT patients. RCF was lower in patients with PV (245 ± 51 vs 306 ± 49; p = 0.032) and it correlated significantly with red blood cell count in this group (r = -0.44; p = 0.012). There were no differences in parameters of retinal morphology between the groups. There was a significant difference in renal RI between PV and EHT groups (0.67 ± 0.06 vs 0.61 ± 0.07; p = 0.033). Conclusions: Patients with PV were characterized by lower indices of sympathetic nervous system activity and a tendency towards lower serum aldosterone concentrations. Alterations of retinal and renal perfusion in PV were also observed.